analisis kinerja simpang tiga ruas jalan sunan kudus-jalan kyai telingsing, kabupaten kudus - widodo, slamet (Jurnal Civil Engineering Study, 2023)
Kudus Regency is a Regency located in Central Java Province, Indonesian. Jalan Sunan Kudus is a road that connects Kudus Regency and Jepara Regency. The road a fast lane because it is a local route. Not only cars and motorbike use this route, trucks and buses also use this route as yhe main route. This unsignalized intersection is an intersection that connects Jalan Sunan Kudus and Jalan Kyai Telingsing. Jalan Sunan Kudus as the Main Street and Jalan Kyai Telingsing as the minor road. The condition of the intersection is a fairly congested intersection because the main road is used as a link between districts, besides that it is also used as access to the tomb of Sunan Kudus and the Menara Kudus Mosque. So services for tourists and pilgrims who come from outside that city and within the city who pass through the intersection have the potential to experiences congestion. The survey was carried out using manual techniques in the data collection process in the field. This analysis uses the calculation technique MKJI 1997.